Nursing handover in the Indonesian hospital context: Structure, process, and barriers - Krisna Yetti; Nani Asna Dewi; Sri Herni Wigiarti; Dina Warashati (Belitung Nursing Journal, 2021)
Background: Nursing handover is an essential part of nursing practice to safe patient care, which occurs among nurses between shifts for transferring professional responsibility and accountability. However, there is limited information about the implementation and evaluation of nursing handover in Indonesian hospitals.  Objective: This study aimed to describe the structures, processes, and barriers of the nursing handover in the Indonesian hospital context.  Methods: This study employed a case study design in five inpatient units, especially in the medical-surgical wards of a referral hospital in Indonesia. The study was conducted from August to November 2018. A total of 100 handovers and 76 nurses were included. Focus group discussions were conducted in head nurses, nurse team leaders, and registered nurses. Observations were implemented to capture the handover process, including the number of the nurses in and out and the content of the information covered situation, background, assessment, and recommendations (SBAR). Data were analyzed using content analysis and fishbone analysis. Results: The nursing handover consisted of three phases: before, during, and after. The handover barriers were divided into manpower, material, money, method, environment, and machine. The content of handover varied according to nurses’ familiarity with the patients and their complexity. The nurses also actively participated during the handover process, although some nurses were absent in the handover time. About 75% of nurses had sufficient knowledge about the shift handover process using SBAR. The SBAR was adopted as a standard for handover, but no specific guideline or standard operating procedure. Conclusion: The results of this study can be used as basic information to develop a guideline of nursing handover and supervision in the context of hospitals in Indonesia and beyond.